Miniscrew-supported coil spring for molar uprighting: description - Antônio Carlos de Oliveira Ruellas; Matheus Melo Pithon; Rogério Lacerda dos Santos (Dental Press Editora, 2013)
INTRODUCTION: Since the beginning of miniscrews as orthodontic anchorage, many applications have been described in the literature. Among these, one is the uprighting of mesially inclined molars. In regard to the mechanical aspects, however, there is little information about the application of orthodontic forces using such devices. OBJECTIVE: The objective of this study was to describe a miniscrew supported spring for uprighting of mesially inclined molars. With this device, one can achieve the correct use of orthodontic biomechanics, thus favoring more predictable tooth movements and preventing unwanted movements from occurring. INTRODUÇÃO: desde o surgimento dos mini-implantes como recurso de ancoragem ortodôntica, muitas aplicações têm sido descritas na literatura. Entre essas, cita-se a verticalização de molares inclinados para mesial. No entanto, pouco se fala da correta aplicação das forças ortodônticas nesses dispositivos, sob o ponto de vista mecânico. OBJETIVOS: o objetivo desse artigo foi demonstrar uma mola mini-implante suportada para verticalizar molares inclinados para mesial. Com esse dispositivo consegue-se correta aplicação da mecânica ortodôntica, favorecendo movimentos mais previsíveis e minimizando os movimentos indesejáveis.